CRANE CABINS’ SAFETY AND ERGONOMICS CHARACTERISTICS EVALUATION BASED ON DATA COLLECTED IN SWEDEN PORT - Spasojević-Brkić, Vesna K; Veljković, Zorica; Brkić, Aleksandar (Journal of Applied Engineering Science, 2015)
This paper presents an evaluation of crane cabins safety and ergonomics characteristics. It is based on previous research data collected for benchmarking analysis for crane cabins operating in one port in Sweden. Six crane cabin types are examined regarding eight characteristic divided in three groups: operator-control devices interaction, safety and anthropometric adjustment according to needs weighting data. Primary analysis of those data was conducted using Pareto analysis. Further analysis are done using developed indexes of characteristics performances while final conclusions were drawn for characteristic of crane cabins using crane index of performance. Taking into account all examined crane cabins only 52.5% of operator- control devices interaction, 75% of safety and 60% of anthropometric adjustment issues are satisfied in current designs.